Real-world treatment persistence of non-tumor necrosis factor inhibitors versus tumor necrosis factor inhibitors among patients with rheumatoid arthritis in South Korea. (1st February 2020) - Park, Jae-A; Lee, Min-Young; Nam, Jin Hyun; Shin, Ju-Young; Wood, Robert; Holbrook, Tim; Kwon, Sun-Hong
Abstract: Aims: We aimed to assess treatment persistence of tumor necrosis factor (TNF) inhibitors and non-TNF inhibitors in two groups of rheumatoid arthritis (RA) patients: biologic disease-modifying antirheumatic drug (bDMARD) initiators and switchers. Patients and methods: This retrospective cohort study utilized a national health insurance claims database. Patients aged ≥18 years initiating/switching bDMARD between 1 December 2013 and 31 December 2014, the index period, were followed for 12 months. Initiators who began treatment with a bDMARD during the index period were defined as having no bDMARD prescriptions for the previous year. Switchers who changed treatment from the previous bDMARD to the index bDMARD were defined as having different bDMARDs during the index period. Treatment persistence rates during the follow-up period were measured, and factors associated with non-persistence were assessed with the Cox proportional hazard model. Results: Of 2684 patients, treatment persistence rates were the highest for abatacept in initiators (69.3%) and tocilizumab in switchers (77.0%), while adalimumab showed the lowest persistence rates for both initiators and switchers (48.2%, 28.8%), followed by etanercept (51.3%, 41.0%). Adalimumab and etanercept were significantly more likely to show non-persistence (HR 1.58, 95% CI 1.27–1.96; HR 1.42, 95% CI 1.14–1.76) compared to infliximab for initiators, while tocilizumab was significantly more likely to show persistence (HR 0.411, 95% CI 0.206–0.819) in switchers. Conclusions: Non-TNF inhibitors showed higher persistence rates than TNF inhibitors in South Korean RA patients, and tocilizumab especially was associated with higher persistence in patients with inadequate response to TNF inhibitors. Good persistence with non-TNF inhibitors indicates the potential for long-term efficacy as first-line treatment.